2007
DOI: 10.1348/147608306x107593
|View full text |Cite
|
Sign up to set email alerts
|

Course of improvement over 2 years in psychoanalytic and psychodynamic outpatient psychotherapy

Abstract: Strategies for the optimal allocation of valuable therapeutic resources should be reconsidered. An adaptive, outcome-oriented allocation strategy of therapeutic resources is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 23 publications
3
29
0
3
Order By: Relevance
“…41 It is unclear why high distress would positively influence treatment outcome, although some have suggested that it may motivate patients to work harder in therapy. 42 We believe it may reflect the law of initial value, or regression to the mean, in that there is a greater likelihood of improvement when baseline levels of distress are high. 43 However, the importance of this finding is in showing that highly distressed patients did not deteriorate in day treatment, but in fact experienced considerable success.…”
Section: Discussionmentioning
confidence: 96%
“…41 It is unclear why high distress would positively influence treatment outcome, although some have suggested that it may motivate patients to work harder in therapy. 42 We believe it may reflect the law of initial value, or regression to the mean, in that there is a greater likelihood of improvement when baseline levels of distress are high. 43 However, the importance of this finding is in showing that highly distressed patients did not deteriorate in day treatment, but in fact experienced considerable success.…”
Section: Discussionmentioning
confidence: 96%
“…Is the superiority of our knights still evident, and if so in what respect? The study of private insurance cases I mentioned earlier (Puschner et al, 2007) would suggest caution. When psychoanalytic psychotherapy and psychodynamic psychotherapy were tracked over two years in 480 patients no significant differences were seen in the rate or extent of decline between these two groups.…”
Section: The Story Of Long-term Psychodynamic Psychotherapymentioning
confidence: 98%
“…There is even some indication, good magic turning bad, of inadvertent harm being done to patients with some personality disorders if they are offered time-limited treatment, so that they end up worse off than when they started (Tyrer et al, 2004). The most recent German work from the bees in Horst Kaechele's hive, a champion beekeeper of psychotherapy research, carefully following a group of patients with private health care insurance, reported that about one and a half years of treatment was required before the average patient achieved an acceptable level of improvement (Puschner, Kraft, Kachele, & Kordy, 2007). Incidentally, this work found no evidence for the much cited exponential rate of improvement originally demonstrated by Ken Howard (Howard, Kopta, Krause, & Orlinsky, 1986).…”
Section: [Page 24 ]mentioning
confidence: 99%
“…Third, the definition of a clinical case is crucial in this discussion. In this, we followed other studies (Blomberg et al, 2001;Derogatis & Lazarus, 1994;Puschner et al, 2007;Sandell et al, 2000) and tried to make an even more conservative estimate of the number of clinical cases. This was done by adding the criteria that a person would be considered a clinical case if this shows on several symptom questionnaires and/or several MMPI-2 clinical scales and/or several Rorschach Special Indices.…”
Section: Bulletin Of the Menninger Clinicmentioning
confidence: 99%
“…Furthermore, we examined whether or not our patients could be identified as clinical cases according to specific criteria. In this, we followed other researchers who had shown that it is possible to use statistically defined cutoff values and combine different instruments to come to a global assessment of the percentage of clinical cases in a certain patient population (Blomberg et al, 2001;Puschner, Kraft, Kächele, & Kordy, 2007;Sandell et al, 2000).…”
Section: Bulletin Of the Menninger Clinicmentioning
confidence: 99%